Nanorobot: Modelling And Simulation. - Senanayake, Arosha; Sirisinghe, R. G.; Shih Mun, Phang (2007)
This research addresses the state of the art in nanorobot design and simulation focusing on the leukemia disease as well as ongoing applications on addressing the challenges posed by cancer treatment, especially chemotherapy.